2008
DOI: 10.1111/j.1742-481x.2007.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection rate and associated risk factors in elective general surgery at a public sector medical university in Pakistan

Abstract: This prospective study aimed to determine the surgical site infection (SSI) rate and associated risk factors was carried in a general surgical ward at Liaquat University Hospital Jamshoro. A total of 460 patients requiring elective general surgery from July 2005 to June 2006 were included in this study. All four surgical wound categories were included. Primary closure was employed in all cases. Patients were followed up to 30th day postoperatively. All cases were evaluated for postoperative fever, redness, swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
34
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 22 publications
9
34
1
Order By: Relevance
“…Risk factors for surgical site infection in the current study were similar to those found elsewhere 10,11 . The one exception was the operation classification of caesarean section, where the range of SSI rates generally falls between 1.6 and 7.4% 12,13 .…”
Section: Discussionsupporting
confidence: 79%
“…Risk factors for surgical site infection in the current study were similar to those found elsewhere 10,11 . The one exception was the operation classification of caesarean section, where the range of SSI rates generally falls between 1.6 and 7.4% 12,13 .…”
Section: Discussionsupporting
confidence: 79%
“…SSIs are responsible for the increasing costs, morbidity and mortality associated with surgical operations and continue to be a major problem, even in hospitals with the most modern facilities and standard protocols for pre-operative preparation and the administration of antibiotic prophylaxis [21]. The reported rates of SSIs prevalence are as low as 2.5% and as high as 41.9% [22,23]. The high percentage of positive samples obtained in our study can be attributed to the following factors.…”
Section: Discussionmentioning
confidence: 99%
“…Sangrasi et al [44] performed a prospective study of 460 patients undergoing general surgical procedures at a university-affiliated hospital in Pakistan to quantify the incidence of and identify risk factors for SSI. The overall SSI rate was 13.0%.…”
Section: Mixed-category Seriesmentioning
confidence: 99%